Spatial and temporal population genomics of Phoenicopterus ruber (American Flamingo) - Folsom, Jessica; Whitfield, Steven; Fitak, Robert; Frias Soler, Roberto Carlos; Wink, Michael; Alvarado-Bremer, Jaime; Migoya, Rodrigo; van Slobbe, Frank; Cant, Shelley; Hoffman, Eric (Ornithological applications, 2025)
Understanding patterns of genetic diversity and connectivity over time is essential when planning for the recovery of an extirpated population. However, this information is not always known since populations are often assessed only after appreciable population reduction has taken place. Phoenicopterus ruber (American Flamingo) present an ideal opportunity to investigate how local extirpation events influence within-population diversity and genetic structure for a recovering population. Phoenicopterus ruber were heavily threatened by hunting and habitat loss throughout the 19th century, which resulted in extirpation of the Florida population by the early 1900s. Despite high vagility and the presence of nearby flocks in the Caribbean, the Florida population has yet to show substantial recovery. In this study we sampled P. ruber across their range and used whole-genome sequencing of historical samples maintained in museum collections, as well as contemporary samples of wild and ex-situ individuals, to estimate genetic diversity, reconstruct gene flow, and evaluate population structure over time. We found nucleotide diversity increased over time for all studied populations while heterozygosity decreased, which could indicate directional selection or potential population structuring. The population structure of flamingos was found to be unaffected by extirpation, with both contemporary and historical samples showing evidence of panmixia, with possible signatures of differentiation between the southern Caribbean population versus other locales. The ex-situ population had higher diversity compared to wild birds and were not significantly differentiated from the wild population, making these flocks possible sources for reintroduction projects. This study highlights the importance of museum collections and whole-genome sequencing to inform the conservation and management of P. ruber in their formerly extirpated range.Over the past century, Phoenicopterus ruber (American Flamingo) have experienced significant threats from hunting and habitat destruction, resulting in decreasing population sizes.The flamingo population in Florida, USA, was reduced to essentially zero and has been slow to recover.We used genomic data gathered from modern, historical, and captive-bred flamingos to determine the current status of the population and assess various recovery strategies.Flamingo populations around the Caribbean show few genetic differences between one another, as well as between wild and captive-bred birds.Areas that were most affected by population declines also demonstrated the most significant loss of genetic diversity.Flamingos represent an important cultural and ecological organism, and little is known about how the species is recovering after population declines.Our research provides insight into the consequences of population declines, and we suggest effective strategies to aid in the recovery process.
Veröffentlicht: 25. Oktober 2025
Gesehen am 28.01.2026